Competitive Advantage Through Positioning Strategy ith Indirect Effects: Study Of Outlet Business In Rest Area Jakarta-Cikampek Toll Road West Java Indonesia - Joseph M.J.Renwarin (International Journal of Science, Technology & Management, 2021)
The objective of this paper is give analysis about current condition of businesses in rest area at toll road in the West Java. The destination of toll road divided by two point, the first, to Bandung city through access to center Java by south Java island route and the second, to Cirebon city through access to center Java by north Java island route. The impact of the open new access is have many opportunities business in the rest area. Every business owner and management try to create the best strategies for sustain by the increase of revenue. Starbuck is one of the sucsess outlets in that. Therefore, this research try to find the impact of importance, communicability and affordability on customer purchase decision. The methodology of this research is exploratory research with the object of research is the customers of Starbuck outlet in rest area KM 19 as the respondents. The datas collecting from focus group discussion (FGD), some interviews to manager, questionare disbursement. The results of research are the influence purchasing decisions at point of r table numbers R of 0.639 is obtained. The communicability is the big influential variable on customer purchase decision.